Historic Scotland’s Backlog Project and the Projects Database - Barclay, Gordon J; Owen, Olwyn (Proceedings of the Society of Antiquaries of Scotland, 1996)
The removal of the backlog of unpublished excavations funded or encouraged by Historic Scotland over the last two decades has been managed within the normal rescue archaeology programme. Sympathetic help has been offered to the directors of these excavations, and the potential problem of a ‘logjam’ in publication will be overcome.